PS-021 Prescription errors in oral investigational products for oncohaematologic outpatients included in a clinical trial. (14th February 2016) - Montero, B; Cuesta, I; Pueyo, C; Navacerrada, MI; Palomar, C; Molina, A; Garea, J; Bermejo, T
Abstract : Background: Prescribing faults and errors in the act of writing can be harmful to patients. There are many studies on errors in manual prescriptions for chemotherapy or medications for inpatients, but there are not many about prescriptions of investigational products. Purpose: To quantify and analyse errors in oral investigational product (oral IP) prescriptions for oncohaematologic outpatients included in a clinical trial (CT). Material and methods: A descriptive and prospective study was conducted from August to September 2015. Inclusion criteria: oral IP prescriptions for outpatients from the oncology and haematology departments. Data about investigators and service, CT code and title, and investigational products requested (strength, dosage, quantity, kit number, etc) were collected in our oral IP prescription formulary. We established 4 error categories for each item to complete from the prescription formulary: erroneous data, omitted data, incomplete/unreadable data and wrong location data. Measured variables were: service, number of oral IP prescribed, and number and type of mistakes. Results: 253 prescriptions from 69 different CTs were analysed; 74.5% were from the oncology department. 1681 errors (5.4 ± 1.8 errors/oral IP) were detected. The mean of errors for the oncology prescriptions was 5.3 ± 1.8 errors/oral IP and 5.9 ± 1.8 errors/oral IP for the haematology prescriptions. The most frequent errors were due to omission of data (1159, 68.8%) and incomplete/unreadable data (318, 18.9%). Others were related to wrong location (123, 7.4%) and erroneous data (81, 4.8%). Of the total number of errors, 19.5% were data about investigators and service (1.1 ± 1.2 errors/oral IP), 25.6% about the CT's code and title (1.4 ± 0.8 errors/oral IP), and 54.8% about oral IP requested (3.0 ± 1.2 erros/oral IP). Conclusion: The high prevalence of errors highlights the necessity to take measures to reduce errors, such as assisted electronic prescription, what can be particularly beneficial for oral IP prescription. A large percentage of these errors are preventable, and awareness of this issue among healthcare professionals plays a key role in promoting effective safety practices to reduce their incidence. References and/or Acknowledgements: Gramage Caro T, Palomar Fernández C, Pueyo López M, et al . Validación de una clasificación de errores de medicación para su utilización en quimioterapia. Farm Hosp 2011;35:197-203 No conflict of interest.